A call for discussion on stereotypic behavior. Issue 2 (3rd July 2022) - Leaf, Justin B.; Cihon, Joseph H.; Javed, Asim; Klick, Sheila; Ferguson, Julia L.; Milne, Christine; Creem, Ashley; Arthur, Shannon; Saunders, Melissa, S.; Olive, Melissa L.; Ross, Robert K.; Leaf, Ronald; et al.
ABSTRACT: Researchers and interventionists, particularly behavior analysts, have a long history of empirically evaluating and clinically implementing interventions related to stereotypic behaviors for autistics/individuals diagnosed with autism spectrum disorder. Despite evidence of the effectiveness of these procedures in decreasing stereotypic behaviors and establishing adaptive competing repertoires, some neurodiversity activists have increasingly expressed concerns about interventions related to stereotypic behaviors. The purpose of this paper was to recognize some of the issues raised by various sources, underscore the importance of including consumers in the selection of goals and methods of intervention from a social validity perspective, discuss balancing concerns with the right to effective behavioral treatment, and consider areas of overlap, reconciliation, and discourse. We urge behavior analysts to continue to include relevant consumers in the selection of goals and intervention, ensure effective behavioral treatment, and approach addressing stereotypic behavior from a place of compassion and caring for our clients.